2009
DOI: 10.1007/s10443-009-9105-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steam Environment on Creep Behavior of Nextel™610/Monazite/Alumina Composite at 1,100°C

Abstract: The tensile creep behavior of a N610™/LaPO 4 /Al 2 O 3 composite was investigated at 1,100°C in laboratory air and in steam. The composite consists of a porous alumina matrix reinforced with Nextel 610 fibers woven in an eight-harness satin weave fabric and coated with monazite. The tensile stress-strain behavior was investigated and the tensile properties measured at 1,100°C. The addition of monazite coating resulted in~33% improvement in ultimate tensile strength (UTS) at 1,100°C. Tensile creep behavior was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…Results of this study are in good agreement with those reported for Nextel ™ 610 fiber tows and single filaments at 1100°C and 1090°C . Results for oxide–oxide CMCs with Nextel ™ 610 fibers also have similar MG parameters. The rupture time of the Nextel ™ 610/alumina CMCs at 1100°C can be predicted from the MG relationship determined for Nextel ™ 610 fibers, as previously demonstrated for prediction of the creep lifetimes of a woven Nextel ™ 610/aluminosilicate CMC .…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Results of this study are in good agreement with those reported for Nextel ™ 610 fiber tows and single filaments at 1100°C and 1090°C . Results for oxide–oxide CMCs with Nextel ™ 610 fibers also have similar MG parameters. The rupture time of the Nextel ™ 610/alumina CMCs at 1100°C can be predicted from the MG relationship determined for Nextel ™ 610 fibers, as previously demonstrated for prediction of the creep lifetimes of a woven Nextel ™ 610/aluminosilicate CMC .…”
Section: Resultssupporting
confidence: 88%
“…The MG plot of the creep‐rupture data obtained in this work is shown in Fig. , where published results for Nextel ™ 610 fibers and for Nextel ™ 610/alumina CMCs are included for comparison. The MG plot in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current oxide‐oxide CMCs are stable up to 1100 or 1200°C in air, but the wide variety of environments and temperatures they may be exposed to during processing and use, particularly in combustion environments, is still of great concern. For example, CMCs that contain Nextel™ 610 fibers (alumina) have higher creep rates and shorter creep rupture times in steam . CMCs that contain Nextel™ 720 fibers (alumina‐mullite) have higher creep rates and shorter creep rupture times in steam and in argon .…”
Section: Introductionmentioning
confidence: 99%